2023
DOI: 10.3389/fonc.2023.1063636
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA epigenetics: The significance of m6A and m5C lncRNA modifications in cancer

Abstract: Most of our transcribed RNAs are represented by non-coding sequences. Long non-coding RNAs (lncRNAs) are transcripts with no or very limited protein coding ability and a length >200nt. They can be epigenetically modified. N6-methyladenosine (m6A), N1-methyladenosine (m1A), 5-methylcytosine (m5C), 7-methylguanosine (m7G) and 2’-O-methylation (Nm) are some of the lncRNAs epigenetic modifications. The epigenetic modifications of RNA are controlled by three classes of enzymes, each playing a role in a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 94 publications
1
12
0
Order By: Relevance
“…In addition, our ndings support the idea that the expression of longWAKMAR2 is also in uenced by m 6 A methylation, since we observed increased methylation levels in WAKMAR2 harboring the IBD risk allele, as well as an induction of overall methylation, in response to in ammation. This is consistent with previous research in which it has been shown that m 6 A methylation undergoes alterations in IBD (3) and can effectively regulate the expression and function of lncRNAs (17,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our ndings support the idea that the expression of longWAKMAR2 is also in uenced by m 6 A methylation, since we observed increased methylation levels in WAKMAR2 harboring the IBD risk allele, as well as an induction of overall methylation, in response to in ammation. This is consistent with previous research in which it has been shown that m 6 A methylation undergoes alterations in IBD (3) and can effectively regulate the expression and function of lncRNAs (17,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have determined lncRNAs can be regulated by m 5 C-related to participate in the biological process of tumors by regulating of RNA localization, stability, and transcription efficiency [ 28 ]. Referring to the summarized list reviewed by Cusenza et al, a large number of lncRNAs have been verified as signatures modified by m 5 C in malignancies, especially for squamous cell neoplasms [ 29 ]. For HNSCC patients, a reliable signature for prognostic prediction and immune infiltration assessment is necessary to develop an individual and precise treatment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lncRNA HOTAIR interacts with the PRC2 to promote the trimethylation of H3K27me3, inhibiting target gene transcription. 24,25 It is believed that lncRNAs regulate downstream gene transcription and influence specific signaling pathways when different stimulating conditions are applied. In additional, the lncRNA is used as a decoy because after it is translated, it directly binds to some protein molecules, such as proteins involved in chromosome folding or transcription regulators, and interferes with their functions.…”
Section: The Role Of Lncrnas In Cancermentioning
confidence: 99%